Viscoelasticity of frozen/thawed egg yolk - Telis, VRN; Kieckbusch, T. G. (Wiley-Blackwell, 1997)
Dynamic rheological measurements indicate that the gel formed during freezing is based on physical aggregation rather than chemical binding, with a nonhomogeneous structure. The gelation was highly dependent on frozen storage temperature in the range -10 to -14 degrees C, but there was no appreciable difference in the range -14 to -24 degrees C. When yolk was maintained motionless and supercooled at -10 degrees C and -12 degrees C for 23 hr, no change in the complex modulus, G*, was observed, but there was a considerable increase when yolk was disturbed and became frozen at the same temperatures for the same time.
Keywords: egg yolk; freezing; gelation; viscoelasticity